Sea Turtle Conservation - a Goan Scenario - Kumar, Shashi (Indian Forester, 2002)
Though the history of Forest Department's involvement in Sea turtle conservation is not very old in Goa, the community based conservation programme of Goa Forest Department has given a new dimension to this conservation programme. Within a period of four years viz. 1997-98 to 2000-01 the programme has taken a big leap forward. Though there are no mass nesting beaches in Goa, this tiny State on the West Coast, is now well placed on the Sea turtle conservation map of India.